L’érosion De La Falaise De Sidi Bouzid (Côte Atlantique Marocaine) : Quantification Et Évolution Spatio-Temporelle - Soukaina Khouaja; Mohamed Ouadia; Imane Mourabiti; El Mehdi Irzan (European Scientific Journal, ESJ, 2016)
The study of the coastal cliff "F1" of Sidi Bouzid shows that it is discontinuous, high, complex and very exposed to the marine dynamics. It is subdivided into two sectors in total, consisting of five zones. A second small cliff "F2" is visible, at the foot of F1 during the storms. These two cliffs bear witness to an oscillation of sea level during the Recent Quaternary. This work shows also a clear close relationship between the quantity and the quality of the blocks, on the one hand, and the nature of the fairly limited space on which have accumulated on the other hand. At the stratigraphic level, the cliff in the Northeast sector is characterized by alternating beds of limestone and Cretaceous Marly levels with evidence of tectonic activity. In the Southwest, Quaternary is dominated by mainly continental deposits, with caliches, overcoming the Cretaceous limestones. The block settings are variable and influenced by the height of the cliff. The degree of fragmentation of blocks during their fall affects their shape: elongated (zone V) because little fragile joints and resistance as well as thick banks of limestone or less elongated because hardness of the platform and fragile joints (zone I). Reflecting that blocks inherit, their form of the morphology, structure and lithological nature of the formations that make up. Quantitatively, the number, density and the volume of blocks are variable and proportional but important (I and V zones) of active erosion due to exposure of the cliff to the marine dynamics. However, the number and low density with the high volume of blocks (zone III) reflect indurated and lithological nature (caliches) but less rich in joints of Quaternary deposits On the indices of the blocks, they show little variation but a slight peculiarity of zone V (extended blocks). The layout of blocks shows a difference between blocks of the Northeast and the Southwest sector due to the different orientation of the cliffs but also the turn and the onslaught of the waves in zone III. This study also shows a clear decrease in the cliff and the risk that it is requiring for its protection.